PRESERVICE ELEMENTARY TEACHERS' SELF-EFFICACY AND ATTITUDES FOR TEACHING OF READING-WRITING - Bozgün, Kayhan (International Online Journal of Education and Teaching, 2022)
Teaching of reading-writing is a basic course for preservice elementary teachers. Before starting their pedagogical professional life, preservice teachers are expected to have high self-efficacy and attitudes towards the course. This study aims to determine the relationship between self-efficacy and attitudes towards teaching of reading-writing. In the sub-objective of the study, the differences according to the variables of gender, grade level, daily reading level, and level of like to teach were examined. The sample of the study was determined by maximum sampling, one of the purposeful sampling methods. In this context, 224 preservice teachers participated study in the fall and spring semesters of the 2021-2022 academic year of the education faculty of a state university in the Central Black Sea Region. To collect the data, "Self-Efficacy Scale Towards Reading and Writing Teaching" and "Attitude Scale for Primary Reading and Writing Teaching" were used. In addition, some demographic information was included at the beginning of the data collection form. SPSS 24 program was used in the analysis of the data; independent samples t-test was used in bivariate groups and One-Way Analysis of Variance was used in triple groups. Relationships between dependent and independent variables were tested using multiple regression analysis. Pearson Correlation Coefficient analysis findings were examined to determine which sub-dimensions of the self-efficacy scale should be included in the multiple regression equation. The findings of the study revealed that the self-efficacy of preservice elementary teachers differ according to gender, class, and daily reading levels. A difference was determined in the attitude scores of the preservice teachers according to the variables of gender and like to teach. According to the results of multiple regression analysis, it was concluded that the attitudes of preservice teachers with high self-efficacy in teaching of reading-writing were higher.